Structural analysis of Cu substituted Niin Ni-Zn Ferrite - Parajuli, Deependra; Samatha, K (BIBECHANA, 2021)
Ni-Zn ferrites are soft ferrites basically popular for high-frequency devices. They have low coercivity, low permeability, and higher resistivity. These properties have their own benefits on one hand but on the other hand, we can make them more efficient by doping suitable elements in order for tuning their properties for other applications. In this work, highly conducting Cu is used for substituting Ni in Ni-Zn ferrites and prepared Ni0.5-xCuxZn0.5Fe2O4 (x = 0, 0.05, 0.1, 0.15, and 0.2) samples using the sol-gel auto-combustion process. We have studied their resulting structural parameter using X-ray Powder Diffraction (XRD) and Fourier Transform Infrared (FTIR) Spectroscopy method and compared with that of Cu substituted Zn Ni-Zn ferrites. Their structures are found to be single-phase cubic spinel similar to that of Cu substituted Zn. The lattice constant increases with Cu concentration opposite to that at Zn substitution. Likewise, the size of the crystallites was not in monotonic change with the doping concentration in both cases due to internal strain and cation distribution. The difference in the pattern of XRD and FTIR of our samples indicate their different but significant properties. The changes in the structure show the effect of Cu doping and indicate the possible interesting changes in their electric, electronic, and magnetic properties. BIBECHANA 18 (1) (2021) 128-133